The use of reflection-in-action by adult educators: An inquiry into Schon's’s epistemology of practice - Natalie M. Ferry (Adult Education Research Conference, 1995)
This qualitative study documented the use of reflection-in-action by adult educators in problematic situations. The results demonstrated that novice and experienced reflecting educators use reflecting-in-action and reflecting-on-action as a means to develop expertise. The results indicated that experience alone is not the "master teacher" of the reflective process.